2022
DOI: 10.1002/iid3.612
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal profile of neutralizing and binding antibodies in vaccinated and convalescent COVID‐19 cohorts by chemiluminescent immunoassays

Abstract: Introduction Surrogate rapid serological assay was urgently demanded for accessibly interpretation of immunity potency and duration of neutralizing antibody against SARS‐CoV‐2. The longitudinal trajectory of antibody profile with a reliable large‐scale assay was crucial to judge the protective immune status, avoid futile therapy and provide insight into the booster vaccination minimizing the risk of COVID‐19. Methods A total of 195 volunteers were enrolled for a two‐doses procedure (0 and 28 days) of inactive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 27 publications
3
7
0
Order By: Relevance
“…This is in agreement with another study, in which most plasmas obtained from individuals recovering from COVID-19 did not contain high levels of neutralizing activity [ 37 ]. In contrast to the finding that vaccination induces the production of abundant neutralizing antibodies, this has been confirmed by a previous study [ 38 ]. The determination of the immune correlates of protection against SARS-CoV-2 is necessary to predict the decrease in antibodies and determine vaccination strategies.…”
Section: Discussionsupporting
confidence: 78%
“…This is in agreement with another study, in which most plasmas obtained from individuals recovering from COVID-19 did not contain high levels of neutralizing activity [ 37 ]. In contrast to the finding that vaccination induces the production of abundant neutralizing antibodies, this has been confirmed by a previous study [ 38 ]. The determination of the immune correlates of protection against SARS-CoV-2 is necessary to predict the decrease in antibodies and determine vaccination strategies.…”
Section: Discussionsupporting
confidence: 78%
“…Several studies show fair agreement between the cPass ELISA method and chemiluminescent immunoassays ( Nandakumar et al, 2021 ),( Nam et al, 2021 ),( Dou et al, 2022 )( Valdivia et al, 2021 ), plaque reduction neutralization tests ( Taylor et al, 2021 ) or other competitive ELISA methods ( Krüttgen et al, 2022 ). Duan et al compared the cPass ELISA method with a dual-detection fluorescence immunochromatographic assay in 266 serum samples, and found fair agreement (Kappa: 0.82, OPA: 91%) ( Duan et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…The invasion of host cells by the virus mainly depends on the RBD of the spike protein 11 . As the gold standard for neutralizing capacity determination, the neutralization assay based on either real virus or pseudovirus is reliable but tedious and time‐consuming 12,13 . The alternative serological test based on RBD–ACE2 interaction has been shown to have high sensitivity and specificity, and a good correlation with the conventional virus neutralization assay 13 .…”
Section: Discussionmentioning
confidence: 99%
“…The neutralizing antibody is considered critical due to its robust correlation with the protective efficacy of a vaccine, and it has also been reported that specific antibody combinations may contribute to maximum neutralization 14 . Total and IgG antibodies, as two subsets of anti‐COVID‐19 antibodies, also play a role in protecting patients recovering from COVID‐19 from reinfection 12 . Fortunately, the total antibody and IgG antibody maintained high antibody titers and had high seropositive rates of 100% and 90.63%, respectively, which suggested that the anti‐SARS‐CoV‐2 antibodies may still provide a certain degree of protection against infection 1 year after the third dose.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation